2018
DOI: 10.1177/0091026017753645
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Change Content, Context, Process, and Leadership in Understanding Employees’ Commitment to Change: The Case of Public Organizations in Kurdistan Region of Iraq

Abstract: In times of financial austerity, public organizations are forced, either by internally motivated goals or externally mandated policies, to implement reforms and changes to cut back on expenses. While organizational change happens with increasing magnitude and frequency in public sector organizations, much of public management research concerning organizational change has mainly focused on change at the sector or national level. This study, on the contrary, focuses on a more micro-level and individual perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 75 publications
2
63
0
4
Order By: Relevance
“…Results showed that participation in decision-making had a variety of effects on several types of change. Participation in decision-making was found to be a significant predictor to affective commitment to change (Ahmad & Cheng, 2018;Soumyaja, Kamlanabhan, & Bhattacharyya, 2011;Van der Voet et al, 2016) and normative commitment to change, but of no relation with continuous commitment to change (Soumyaja et al, 2011). The research conducted by Rogiest et al (2015) and Thien (2019) did not find direct relation between participation with commitment to change.…”
Section: Participation In Period Of Change and Commitment To Changementioning
confidence: 89%
See 1 more Smart Citation
“…Results showed that participation in decision-making had a variety of effects on several types of change. Participation in decision-making was found to be a significant predictor to affective commitment to change (Ahmad & Cheng, 2018;Soumyaja, Kamlanabhan, & Bhattacharyya, 2011;Van der Voet et al, 2016) and normative commitment to change, but of no relation with continuous commitment to change (Soumyaja et al, 2011). The research conducted by Rogiest et al (2015) and Thien (2019) did not find direct relation between participation with commitment to change.…”
Section: Participation In Period Of Change and Commitment To Changementioning
confidence: 89%
“…Active participation would result in positive attitude towards change and required behaviour in change (Lines & Selart, 2013). Various research results showed that participation correlated positively with attitude towards change, such as openness to organizational change (Wanberg & Banas, 2000), individual readiness for change (Bouckenooghe & Devos, 2008;Bouckenooghe, Devos & Van den Broeck, 2009) and commitment to change (Ahmad & Cheng, 2018;Rogiest, Segers, & van Witteloostuijn, 2015; Van der Voet, Kuipers, & Groeneveld, 2016). Also, participation was valued as a form of organizational support towards middle managers (Reeves, Walsh, Tuller, & Magley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such a notion is supported by various scholars who argue that “If people do not change, there is no organizational change” (Schneider et al 1994, 7), or that “change persists over the long term only when individuals alter their on‐the‐job behaviors in appropriate ways” (Choi 2011, 480). Thus, the response of change recipients to changes is, inter alia, suggested to be one of the main determinants of the extent to which organizational changes succeed in public sector organizations (Ahmad and Cheng 2018; Kelman 2005; van der Voet 2016).…”
Section: Figurementioning
confidence: 99%
“…Therefore, the last condition can be relaxed to 'a significant reduction of the direct effect' rather than a complete elimination of the effect. When this is applicable, one speaks of partial mediation [25,26].…”
Section: Resultsmentioning
confidence: 99%